The Holy Reich : - Steigmann-Gall, Richard (Cambridge University Press, 2003)
Analyzing the previously unexplored religious views of the Nazi elite, Richard Steigmann-Gall argues against the consensus that Nazism as a whole was either unrelated to Christianity or actively opposed to it. He demonstrates that many in the Nazi movement believed the contours of their ideology were based on a Christian understanding of Germany's ills and their cure. A program usually regarded as secular in inspiration - the creation of a racialist 'peoples' community' embracing anti-Semitism, anti-liberalism and anti-marxism - was for these Nazis conceived in explicitly Christian terms. His examination centers on the concept of 'positive Christianity', a religion expounded by many in the party leadership. He also explores the struggle the 'positive Christians' waged with the party's paganists - those who rejected Christianity in toto as foreign and corrupting - and demonstrates that this was not just a conflict over religion, but over the very meaning of Nazi ideology itself.